2023
DOI: 10.1049/syb2.12067
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of FBN2 in bladder cancer: A risk factor and the tumour microenvironment influencer

Abstract: Bladder cancer (BLCA) is a common and difficult‐to‐manage disease worldwide. Most common type of BLCA is urothelial carcinoma (UC). Fibrillin 2 (FBN2) was first discovered while studying Marfan syndrome, and its encoded products are associated with elastin fibres. To date, the role of FBN2 in BLCA remains unclear. The authors first downloaded data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). The patients were divided into high FBN2 expression and low FBN2 expression groups, and the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
(82 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that high COL7A1 expression is associated with poor prognosis in clear cell renal cell carcinoma (ccRCC), and in vitro knockdown of COL7A1 expression significantly affects the migratory ability of ccRCC cells [ 25 ]. Other studies have also shown that FBN2, CSPG4 and UNC5C as oncogenes were significantly associated with poor prognosis, which is in line with our findings [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that high COL7A1 expression is associated with poor prognosis in clear cell renal cell carcinoma (ccRCC), and in vitro knockdown of COL7A1 expression significantly affects the migratory ability of ccRCC cells [ 25 ]. Other studies have also shown that FBN2, CSPG4 and UNC5C as oncogenes were significantly associated with poor prognosis, which is in line with our findings [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%